PROBLEMS IN THE PHYSICIAN-PATIENT DYAD - T. V. Pyanzova (Туберкулез и болезни лёгких)
Phthisiatrician-patient cooperation, the efficiency of which largely depends is influenced by the outcome of treatment, is one of the aspects of antituberculosis therapy. This review gives a brief general characterization of studies dealing with physician-patient relationships and details the issues of communication having regard to the specific features of phthisiatrician specialty.